Digital innovation in religious education: Development of a digital book for islamic religious education in vocational school - Arifah, Siti Aisyatul; Fawait, Agus (Journal of Research in Instructional, 2025)
Islamic religious education has an important role in shaping the character and personality of students at school. However, students' enthusiasm for this learning is still relatively low due to several factors, such as monotonous teaching strategies, limited learning tools, and minimal student participation. In the digital era, the utilization of technology, such as the Book Creator application, offers a solution that allows teachers to create interactive digital books with text, images, videos, and audio, which have the potential to increase student attractiveness and engagement in learning. This study aims to design and evaluate the effectiveness of interactive learning media, which is based on the Book Creator application, for teaching Islamic religious education to grade XI students at SMK Negeri 1 Tapen Bondowoso. This research used the Research and Development (R&D) method by adopting the ADDIE development framework. The data was collected through validation from media and material experts, observation, interviews, and validation questionnaires. The results showed that (1) the developed learning media received media expert assessment with an average score of 3.68 (92%) in the "Very Valid" category; (2) material expert assessment with an average score of 3.742 (93.55%) in the "Very Valid" category; and (3) student trial results with an average score of 0.86 (86%). The results show that the interactive learning media based on Book Creator are feasible and effective for use and implementation in Islamic religious education at SMK Negeri 1 Tapen Bondowoso.